Snowbed communities and soil C and N dynamics during a four-year investigation in the NW-Italian Alps - Emanuele Pintaldi; Marco Pittarello; Davide Viglietti; Elena Quaglia; Michele Eugenio D’Amico; Giampiero Lombardi; Nicola Colombo; Michele Lonati; Michele Freppaz (Arctic, Antarctic, and Alpine Research, 2022)
The snowbed habitats represent a relevant component of the alpine tundra biome, developing in areas characterized by a long-lasting snow cover. Such areas are particularly sensitive to climate changes, because small variations in air temperature, rain, and snowfall may considerably affect the pedoclimate and plant phenology, which control the soil C and N cycling. Therefore, it is fundamental to identify the most sensitive abiotic and biotic variables affecting soil nutrient cycling. This work was performed at seven permanent snowbed sites belonging to Salicetum herbaceae vegetation community in the northwestern Italian Alps, at elevations between 2,686 and 2,840 m.a.s.l. During a four-year study, we investigated climate, pedoclimate, floristic composition, phenology, and soil C and N dynamics. We found that lower soil water content and earlier melt-out day decreased soil N-NH4+, N-NO3−, dissolved organic carbon (DOC), dissolved organic nitrogen (DON), total dissolved nitrogen (TDN), microbial nitrogen (Nmicr), microbial carbon (Cmicr), and C:Nmicr ratio. The progression of the phenological stages of Salix herbacea reduced soil N-NH4+ and increased DOC. Our results showed that the snow melt-out day, soil temperature, soil water content, and plant phenological stages were the most important factors affecting soil biogeochemical cycles, and they should be taken into account when assessing the effects of climate change in alpine tundra ecosystems, in the framework of long-term ecological research.